Biomimetic collective total synthesis of bioactive carbazole alkaloids indizoline, mafaicheenamine A, claulamine A, claulansine A, and the proposed claulamine E - Markad, Shivaji B.; N. P. Argade (Journal of Organic Chemistry, 2016)
The common precursor 1-methoxy-2-prenyl-3-carbomethoxycarbazole was synthesized from dimethyl indolylmethylenesuccinate in four steps. Well-planned reductive and/or oxidative transformations and intramolecular cyclizations were performed on a pivotal common precursor to accomplish collective first total synthesis of titled natural products and proposed Claulamine E. Burgess reagent induced formation of kinetically controlled product Claulamine A, and intramolecular cyclizations to form bicyclic claulansine A were the key reactions. An alternatively attempted synthesis failed to provide the structural isomer of proposed Claulamine E.